2021
DOI: 10.1182/blood-2021-145824
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Trial Comparing a Calcineurin Inhibitor-Free Graft-Versus-Host Disease Prophylaxis Regimen with Post-Transplantation Cyclophosphamide and Abatacept to Standard of Care

Abstract: Background: Graft versus host disease (GVHD) is one the major causes of mortality and morbidity after an allogeneic stem cell transplantation. We hypothesized that we can induce post-transplant tolerance by using the combination of post-transplant cyclophosphamide (PTCy) and abatacept (CTLA4Ig) for GVHD prophylaxis. PTCy when given on Days +3 and +4 can eliminate host-reactive donor T cells. CTLA4Ig blocks the costimulatory signals given through CD28 to naïve donor T cells thus favoring an anergic phenotype th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These studies also showed successful GVHD prevention with CTLA4-Ig blockade, leading to abatacept FDA approval in 2021 for select patients undergoing MUD and 7/8 HLA MMUD HCT. Our institutional experience in a randomized clinical trial has also found that omission of CNIs with a prophylactic regimen of PTCy and abatacept significantly decreased risk of acute and cGVHD, with a more favorable toxicity profile compared with traditional GVHD prophylaxis 24 . Furthermore, in haploidentical HCT, a phase 1b-2 clinical trial investigating PTCy and abatacept with CNI tacrolimus found low rates of grades 3 to 4 aGVHD (4.4%) and one year moderate-to-severe cGVHD (25.9%) rates 25 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These studies also showed successful GVHD prevention with CTLA4-Ig blockade, leading to abatacept FDA approval in 2021 for select patients undergoing MUD and 7/8 HLA MMUD HCT. Our institutional experience in a randomized clinical trial has also found that omission of CNIs with a prophylactic regimen of PTCy and abatacept significantly decreased risk of acute and cGVHD, with a more favorable toxicity profile compared with traditional GVHD prophylaxis 24 . Furthermore, in haploidentical HCT, a phase 1b-2 clinical trial investigating PTCy and abatacept with CNI tacrolimus found low rates of grades 3 to 4 aGVHD (4.4%) and one year moderate-to-severe cGVHD (25.9%) rates 25 .…”
Section: Discussionmentioning
confidence: 86%
“…Pre-clinical studies suggest that CTLA4-Ig blockade allows NK cell activity and thus the GVL effect remains preserved. Furthermore, our institutional experience found no significant difference in overall survival (OS), GVHD-relapse-free OS, or disease-free survival in the abatacept arm versus the CNI containing standard-of-care arm at one year post HCT 24 . Collectively this suggests that the GVL effect remains preserved with use of CTLA4-Ig blockade-based GVHD prophylactic regimens.…”
Section: Discussionmentioning
confidence: 96%
“…A different phase II randomized clinical trial (NCT03680092) is comparing GVHD prophylaxis with PTCy and abatacept (CNI-free regimen) with CNI/mini dose MTX in 8/8 MRDs or MUDs. Preliminary results were presented at the 63 rd ASH Annual Meeting in 2021 ( 80 ). In this trial, patients in the PTCy arm received abatacept on days +5, +14, +28, +56, +84, +112, +140, and +168.…”
Section: Examples Of Drugs Applied In General Practicementioning
confidence: 99%